Sostoyanie serdtsa po dannym ekhokardiografiiu lits s ozhireniem, manifestirovavshimv pubertatnyy period (Ожирение и метаболизм, 2011)
47 male patients were included in this study: the group of 17 adolescents with puberty-onset obesity (aged 19,7±0,37 years), the group of 20 adults with puberty-onset obesity (aged 32,25±0,96 years), 10 gender-matched controls (aged 20,8±0,25 years). All subjects underwent echocardiographic and lipid profile examination. Conclusion: Among adolescent males with puberty-onset obesity normal left ventricular geometry was encountered with similar frequency in both subgroups, with and without arterial hypertension. When left ventricular hypertrophy develops, it may be presented as either concentric or eccentric hypertrophy. In men with puberty-onset obesity the of patients, duration of their disease and concomitant arterial hypertension aggravate left ventricular hypertrophy. In men with puberty- onset obesity and arterial hypertension the most common pattern of impaired left ventricular geometry is concentric hypertrophy. Regardless of the presence of arterial hypertension, men with puberty-onset obesity have a tendency to development of left ventricular diastolic dysfunction that may be combined with both concentric and eccentric left ventricular hypertrophy.